Maternal and Perinatal Health in Developing Countries - Hussein, Julia (CABI, 2014)
Acknowledgements are due to my co-editors and the authors for their contributions. Special thanks are due to Victor Ojodale Oga la, Katherine Ritchie and Ann Fitzmaurice for their assist- ance with referencing. The Kambia Appeal, Riders for Health, Paul Kwale, Lorney Kanguru and Navya Bezawada contributed to my search for photographs of transport modalities. This book is a celebration - of what I've learned, and of the tireless efforts of the many, valued friends and colleagues I've learned from, who have dedicated their lives to improving maternal and perinatal health. May there be many others who feel the passion for joining our global 'community'.